Efeito da adubação potássica e da época de colheita na produtividade de canola - Rossetto, C. A. V.; Nakagawa, J. [UNESP]; Rosolem, Ciro Antonio [UNESP] (Sociedade Brasileira de Ciência do Solo, 1998)
A field experiment was carried out to study the effects of potassium fertilization and time of harvesting on canola seed yield. The soil was a Red-Yellow Latosol (Hapludox), and the experimental design was a subplot replicated four times in completely randomized blocks. Potassium levels (0 and 40 kg ha-1 of K) were applied in the plots, and the subplots consisted of 7 weekly harvests, starting 112 days after planting. Yield and yield components were evaluated at each harvest. Although no positive effect of potassium fertilization on seed yield and growth parameters was evident, this fertilization caused higher retention of pods from the harvest at 147 and 154 days after planting. Time of harvesting did not affect seed yield. The maximum level of dry matter of the above ground part of the plants was obtained from the harvest at 112 days, and, of seeds, at 126 days, at high potassium level.

O experimento foi desenvolvido na Fazenda Experimental São Manuel da Universidade Estadual Paulista, Campus de Botucatu, em Latossolo Vermelho-Amarelo fase arenosa, no ano de 1996, com o objetivo de estudar o efeito da adubação potássica e da época de colheita na produtividade de canola (Brassica napus L. var. oleifera Metzg.). O delineamento experimental foi o de blocos ao acaso com parcelas subdivididas, com quatro repetições. As parcelas constituíram-se de duas doses de potássio (0 e 40 kg ha-1 de K), e as subparcelas, de sete épocas de colheita, realizadas em intervalos semanais, no período de 112 a 154 dias após a semeadura. A adubação potássica não favoreceu o crescimento das plantas e a produtividade de sementes de canola, porém acarretou maior retenção das síliquas nas colheitas realizadas aos 147 e 154 dias da semeadura. A época de colheita não resultou em benefício consistente ao rendimento de sementes. O máximo de matéria seca da parte aérea das plantas foi atingido aos 112 dias da semeadura, e o das sementes, aos 126 dias, na presença da adubação potássica.
Canola seed yield as affected by potassium fertilization and harvest time
Keywords: Brassica napus; maturação; potássio; Brassica napus; maturation; potassium levels